1988
DOI: 10.1038/336123a0
|View full text |Cite
|
Sign up to set email alerts
|

Trophic regulation of nerve cell morphology and innervation in the autonomic nervous system

Abstract: A remarkable feature of nerve cells is the complex and variable pattern of their axonal and dendritic branches. Quantitative studies of a simple part of the nervous system in mammals provide evidence that neuronal geometry and innervation are regulated by long-term trophic interactions between neurons and their targets. This trophic linkage may explain how nerve cells adjust their function to the needs of bodies that vary markedly in size and form.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
164
0
4

Year Published

1993
1993
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 329 publications
(171 citation statements)
references
References 33 publications
3
164
0
4
Order By: Relevance
“…At the very beginning, calcium homeostasis disturbances 9 and trophic factor withdrawal 10 occurs after axotomy and participate in this neuronal response. Both events had already been linked to ER stress in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the very beginning, calcium homeostasis disturbances 9 and trophic factor withdrawal 10 occurs after axotomy and participate in this neuronal response. Both events had already been linked to ER stress in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of these trophic factors in turn initiates the cell responses of neurons and surrounding glial after axotomy. 10 The endoplasmic reticulum (ER) is a dynamic network of interconnected membrane tubules that essentially reaches every part of the cell, including dendrites 11 and axons 12 in neurons. ER is associated with microtubules 13 and largely contributes to local calcium homeostasis and signaling, and protein and lipid biosynthesis.…”
mentioning
confidence: 99%
“…In this study, we examined the role of the ERK pathway in the regulation of dendritic growth in sympathetic neurons exposed to BMP-7 and NGF. Costimulation with these two agents leads to a rate of dendritic growth in vitro that is equivalent to that observed in vivo (Lein et al, 1995), and there is evidence for sympathetic neurons being exposed to both of these growth factors in vivo, with NGF being derived from target tissues (Purves et al, 1988) and BMPs being produced by glia .…”
Section: Introductionmentioning
confidence: 95%
“…Recent studies have indicated that the initiation of dendrites is, in part, governed by mechanisms intrinsic to neurons (Dotti et al, 1988;Black and Baas, 1989). In addition, there is ample evidence that extrinsic factors influence neuronal polarity and dendritic arborization (Mudge, 1984;Bruckenstein and Higgins, 1988a,b;Purves et al, 1988;Snider, 1988;Tropea et al, 1988;Chamak and Prochiantz, 1989;Johnson et al, 1989;Lein and Higgins, 1989;Clendening and Hume, 1990;&hilling et al, 1991).…”
mentioning
confidence: 99%